2022
DOI: 10.1161/strokeaha.121.034200
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Enhances Neuroplasticity and Accelerates Motor Recovery in a Stroke Mouse Model

Abstract: Background: More effective strategies are needed to promote poststroke functional recovery. Here, we evaluated the impact of bihemispheric transcranial direct current stimulation (tDCS) on forelimb motor function recovery and the underlying mechanisms in mice subjected to focal ischemia of the motor cortex. Methods: Photothrombotic stroke was induced in the forelimb brain motor area, and tDCS was applied once per day for 3 consecutive days, starting 72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 59 publications
(118 reference statements)
1
23
0
Order By: Relevance
“…64 Experimental rodent studies suggested that tDCS in either polarity might reduce neuronal damage, decrease microglia activity, and enhance functional recovery during the acute or subacute phase after stroke. 18-20,47 Our data suggest that 5 sessions of cathodal tDCS applied ipsilesionally starting the first week after focal cortical stroke is most effective in mice. Additional tDCS sessions on days 12 to 16 after stroke did not benefit recovery, the modulation of neuroinflammation, or neurogenesis.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…64 Experimental rodent studies suggested that tDCS in either polarity might reduce neuronal damage, decrease microglia activity, and enhance functional recovery during the acute or subacute phase after stroke. 18-20,47 Our data suggest that 5 sessions of cathodal tDCS applied ipsilesionally starting the first week after focal cortical stroke is most effective in mice. Additional tDCS sessions on days 12 to 16 after stroke did not benefit recovery, the modulation of neuroinflammation, or neurogenesis.…”
Section: Discussionmentioning
confidence: 71%
“…For future research, we would consider more extensive group sizes, fewer statistical variables, and behavioral tests providing continuous scales such as nest building activity, the cylinder test, or the grip strength test, whose exceptional consistency in detecting functional deficits in mice in the chronic phase after motor cortex lesions has been reported. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the aforementioned reviewed synaptic plasticity modifications induced by tDCS and also the activated molecular cascade underlying these effects, some recent works pointed the attention not only at the functional but also the structural changes ( Paciello et al, 2018 ; Barbati et al, 2020 ; Gellner et al, 2020 ; Longo et al, 2022 ).…”
Section: Transcranial Direct Current Stimulation Modulation Of Struct...mentioning
confidence: 99%
“…Moreover, in a recent preclinical study, Longo et al (2022) applied bilateral tDCS over M1 (35.4 A/m 2 , 20 min, single daily sessions for 3 consecutive days) in a mouse model of ischemic stroke and showed that tDCS accelerated motor recovery by enhancing forelimb strength and ameliorating performances in both skilled and non-skilled motor tasks. The authors looked at possible effects on FC by recording local field potentials through epidurally implanted electrodes over M1 and somatosensory cortices and analyzing total coherence (TotCoh)—an index expressing global functional coupling of the LFP rhythms ( Vecchio et al, 2019 ).…”
Section: Transcranial Direct Current Stimulation and Rewiringmentioning
confidence: 99%